Efeitos energéticos e topológicos no design de cocristais de compostos aromáticos e em 1,5-diaril-1h-pirazol-3-carboxilatos de etila - Belladona, Andrei Lucca (2017)
This work presents the study of the supramolecular environment in multicomponent crystals. Multicomponent crystals were defined by J. D. Dunitz as a crystal containing two or more components together, so that this concept includes cocristais and solvates, these being the molecular models of study in this dissertation. In the first chapter the supramolecular environment of cocristais based on π•••π interactions were studied through the analysis of 10 structures of cocristais already deposited in CCDC database, in addition to its coformers. All cocristals are formed by a halogenated aromatic coformer (octafluoraphthalene, hexafluorobenzene or decafluorobiphenyl) and a polyaromatic or heterocyclic coformer. The electrostatic potential maps of individual coformers demonstrated the electrostatic complementarity between the two components. The coformers and their respective cocristals were evaluated using the methodology of the supramolecular cluster, where the dimers were analyzed by quantum mechanics calculations and the Quantum Theatrical Theory in Molecules data. Intermolecular interactions were hierarchized according to their energies and mechanisms of crystallization were proposed for cocristals and coformers. The analysis of the self-assembly in the coformers and hetero-assembly in the cocrystals resulted in a approach for the formation of cocristals involving π systems. The approach states that "When π systems do not make ππ interactions on the mains dimers (first hierarchies), self-assembly in the coformers, this systems are free to form cocristas based on these interactions." To examine the validity of the approach created a series of heterocycles available in our research group were taken to tests for cocrystallization. Only the self-association of the coformers was evidenced due to the fact that they present ππ interactions in the main dimers, following the trend of the approach created. This work is of extreme importance because its create a simple criteria to select the coformers for the synthesis of cocristais, avoiding the time spent in the laboratory by random combinations. It can be said that, in general, before carrying out a combination for the synthesis of cocristals, it is necessary to analyze the supramolecular cluster of the coformers, if they have CHπ-type interactions in the main dimers they are strong candidates for the synthesis of cocristals. In the second chapter, Ethyl-1,5-Diary-1H-pyrazole-3-carboxilates were used as model compounds for study. The selected compounds have different substituents at the 5-position of the pyrazoline ring (-C6H4-F or -C6H4-Cl), one of which is still obtained as solvate (with water molecules), which made it possible to study the substituents effects and the water molecule effects on the crystalline packing. For the study of the supramolecular environment, the supramolecular cluster was determined through the appropriate methodology and all the dimers were analyzed by calculations of quantum mechanics and data of the Quantum Theatrical Theory in Molecules. Intermolecular interactions were hierarchized according to their energies and crystallization mechanisms were proposed. Based on the proposed crystallization mechanisms, it was possible to show in which stage the water molecules were added to the supramolecular cluster. In addition, this study demonstrated that the change in substituent at the 5-position of the pyrazoline ring, as well as the presence of water, affected the crystalline packing of the compounds, from the first supramolecular dimers. Although water molecules aggregate to the supramolecular cluster only in the fourth hierarchy of interaction, the change in crystalline packing when compared to the solvate molecule and the unsolvated molecule suggests the existence of a balance between the two forms in solution.